A study to evaluate the condition of the periodontal tissues around titanium implants supporting zirconia restorations compared with zirconia restorations with a PEEK base on the opposite side after functional loading - سليمان, بتول; نزيه عيسى,; تهامة يوسف, (Latakia University Journal -Medical Sciences Series, 2024)
This study aims to compare the gingival response around titanium implants supporting zirconium restorations on the one hand and to compare it with zirconium restorations with a polyetheretherketone base manufactured by CAD/CAM on the other hand after one year of functional loading. The research sample consisted of 30 titanium implants distributed among 15 patients with a single posterior tooth loss on each side according to the type of abutment: the posterior loss was compensated by a single titanium implant on each side of the same jaw and after complete healing, i.e. after about three months from surgery, titanium abutments were used in each patient and replaced with zirconium crowns manufactured by CAD/CAM on the one hand and zirconium crowns with a PEEK base manufactured by CAD/CAM on the other hand. Clinical examinations were conducted on the patients during the observation period (4-8-12) months of functional loading. The soft tissue condition around the implants was examined by recording the values ​​of the following periodontal indices: modified plaque index, modified bleeding index, and modified probing depth index. The results showed that the effect of the type of abutment used on the mean gingival bleeding index at probing was not statistically significant, especially after eight or twelve months, and the type of abutment did not show a significant association with the mean probing depth, while the mean plaque index values ​​showed a significant association with the mean probing bleeding. The gingival reactions around zirconium restorations with a PEEK base manufactured by CAD/CAM were almost similar to the gingival reactions around conventional zirconium restorations during the one-year follow-up period.